Identifikasi Jenis-Jenis Lichen dan Lumut di Edupark BP2LHK Banjarbaru: Identify Types of Lichens and Mosses at Edupark BP2LHK Banjarbaru - Sari Indriyani; Norfajrina (Aisha Edutama, 2024)
The aim of the research is to determine the types of moss and lichens found in the Edupark BP2LHK Banjarbaru area, Landasan Ulin sub-district, Banjarbaru City, South Kalimantan. This observation was carried out using roaming and exploration methods around Edupark BP2LHK Banjarbaru. Based on the results of observations and identification of lichens and moss that were carried out at Edupark BP2LHK Banjarbaru, it was found that 9 species of lichens were found and 5 species of moss. From the results of this research, the lichens and mosses found were influenced by the environmental quality found in Edupark BP2LHK Banjarbaru. The environmental quality in Edupark BP2LHK Banjarbaru is still beautiful and well maintained, therefore there are many species of moss and lichens found there.